ANALISIS KESULITAN SISWA DALAM MEMAHAMI TEKS NARASI PADA PELAJARAN BAHASA INDONESIA - Fahtu Rahman, Mugi; Khoiri, Ahmad (PENA KREATIF : JURNAL PENDIDIKAN, 2026)
Reading comprehension is a fundamental skill in Indonesian language learning at elementary school that encompasses the process of understanding and interpreting texts, not merely recognizing letters and words. Narrative texts as one of the learning materials in fourth grade often pose challenges for students due to story structure complexity, limited vocabulary, and low reading interest. This study aims to analyze the difficulties of fourth-grade students at SDN 05 Kotabaru in understanding narrative texts in Indonesian language learning. The research employed a qualitative method with a descriptive approach using observation, interview, and documentation techniques involving 7 students and the fourth-grade teacher. The findings revealed six main difficulties: difficulty understanding text content requiring repeated reading for long texts 5 out of 7 students, limited vocabulary especially words describing actions and emotional states, difficulty understanding plot structure with most confusion at the climax, difficulty finding main ideas 6 out of 7 students, difficulty understanding moral messages as the most challenging aspect 5 out of 7 students showing a gap between literal and evaluative comprehension, and difficulty understanding characters with ambiguous or dynamic characteristics. These difficulties are caused by internal factors (low reading comprehension ability, limited memory capacity, low reading interest) and external factors (overly long and complex texts, limited learning media, non-conducive learning environment). These findings emphasize the need for more varied and systematic learning strategies, particularly in developing evaluative comprehension skills and implicit information interpretation to improve students' literacy quality.